The Incidence and Outcomes of Industrial Action: New Evidence from the 2019 European Company Survey - John T. Addison; Paulino Teixeira (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using the 2019 ECS, we investigate the relationship between union organization, workplace representation, industrial relations quality and strike incidence. We also consider some six issues behind the most recent instances of industrial action or threatened industrial action and their outcomes. Strike incidence is found to be elevated in establishments where union density is higher and where workers are covered by mixed-level collective agreements. Distrust and strained workplace relationships are associated with increased strike incidence, and the converse for an employee-focused business strategy and heightened employee motivation. In discussing the outcomes of different types of industrial action or threatened industrial action specific to the establishment, a distinction is drawn between worker wins, worker retractions/losses, and win-win outcomes, where the default is unresolved outcomes. Higher union density is associated with worker wins, collective bargaining with balanced agreements, and there is now some suggestion that works councils may play a moderating role.
Keywords: J51; J52; J53; 330; strikes; areas and outcomes of conflict; union organization; worker representation; employee-focused strategies; trust; quality of industrial relations